SNOW-COMPACTION EQUIPMENT - LOAD TEST TRAILER. - Goldberg, Sidney L. (1965)
Techniques and equipment have been developed to process snow in place for use as a construction material for roads and runways. A test device to simulate aircraft wheel loadings is needed to determine bearing capacity of the compacted snow and to search out possible processing misses in the material so they can be repaired before landing aircraft. To satisfy this need, a 20-ton semi-trailer was modified to receive two interchangeable aircraft test wheels mounted under the deck. Any desired load up to 38,500 pounds is applied to the test wheel through a power-operated hydraulic system. Ballast placed on the deck of the trailer serves to resist uplift caused by the reaction of the test wheel on the snow. The two test wheels have tires with maximum inflation pressures of 95 and 135 psi. The load test trailer will be used to study bearing capacity of compacted-snow areas near McMurdo, Antarctica, during Deep Freeze 66. (Author)